MicroRNA-31 mediated inhibition of keratin 6 by PSORI-CM01: a novel approach to psoriasis amelioration - Shilei Wang; Jingkai Wang; Helin Pan; Ruogu Yang; Fanli Zeng; Yongfei Fang; Jinwei Zhang (Frontiers in Chemistry, 2025)
BackgroundPsoriasis vulgaris is a serious noncommunicable disease, with no clear cause or cure. Expression of microRNA-31 (miR-31) is significantly increased in the cutaneous tissue of psoriasis vulgaris patients. Keratin 6 (Krt6) serves as a pivotal biomarker in the diagnostic and therapeutic approaches for psoriasis vulgaris. PSORI-CM01, a traditional Chinese medicine formulation comprising seven medicinal herbs, is employed in China for the therapeutic management of psoriasis vulgaris. However, its anti-psoriatic mechanism warrants further investigations. In this study, the underlying anti-psoriasis mechanism of PSORI-CM01dependent of miR-31 and Krt6 was explored.MethodsIn vivo, BALB/c mice were subjected to treatment with imiquimod (IMQ) to establish a psoriasis-like murine model. These psoriasis-like mice were then administered varying concentrations of PSORI-CM01. Following this, evaluations were performed on their Psoriasis Area and Severity Index (PASI) scores, epidermal thickness, and the expression levels of miR-31 and Krt6. HaCaT cells were subjected to treatment with interleukin-6 (IL-6) to create a psoriasis-like cellular model. Following this, the psoriasis-like keratinocytes were administered varying concentrations of PSORI-CM01, and the expression levels of miR-31 were quantified. In addition, these psoriasis-like keratinocytes were transfected with miR-31 mimics and subsequently treated with PSORI-CM01. The expression levels of Krt6 were then quantified and subjected to analysis.ResultsIn vivo, PSORI-CM01 significantly alleviated the clinical-like manifestations of erythema, scales, and thickening in psoriasis-like mice, and it also reduced the PASI scores; Different concentrations of PSORI-CM01 significantly decreased epidermal thickness and the expression of miR-31 and Krt6 in psoriasis-like mice in a dose-dependent manner. In vitro, PSORI-CM01 significantly inhibited the expression of miR-31 and Krt6 in psoriasis-like keratinocytes; However, the decreased Krt6 protein expression was restored by miR-31 mimics.ConclusionPSORI-CM01 may improve psoriasis-like lesions by inhibiting expression of Krt6 protein dependent of miR-31.